Economic development of Central Asia: History and the present day - Duraj, Natasza (2022)
The main goal of the monograph is to present the issues related to the economic and social development of five countries: Kazakhstan, Uzbekistan, Tajikistan, Turkmenistan and Kyrgyzstan. The work consists of seven chapters presenting the history of the economies of individual republics and showing the current situation in each of the analyzed countries.
Keywords: Central Asia; Kazakhstan; Uzbekistan; Tajikistan; Turkmenistan; Kyrgyzstan